Geopolitics: a new field of expertise for buyers. Issue 2 (13th February 2017) - Poissonnier, Hugues
Abstract : Purpose: This paper aims to show the interest of using geopolitical analysis for buyers. Design/methodology/approach: This study is a historical approach. Findings: Geopolitics is very useful for buyers to develop new skills among their suppliers. Originality/value: This paper shows that evolutions of the macro environment are more and more impactful for companies. Taking geopolitical considerations into account is a new key of relevance for purchasing decisions.